Interface Modulation of MoS2/Metal Oxide Heterostructures for Efficient Hydrogen Evolution Electrocatalysis - Hu, Jue; Zhang, Chengxu; Zhang, Yizhen; Yang, Baomin; Qi, Qianglong; Sun, Mingzi; Zi, Futing; Leung, Michael K. H.; Huang, Bolong (Small (Weinheim an der Bergstrasse, Germany), 2020)
Developing efficient earth‐abundant MoS2 based hydrogen evolution reaction (HER) electrocatalysts is important but challenging due to the sluggish kinetics in alkaline media. Herein, a strategy to fabricate a high‐performance MoS2 based HER electrocatalyst by modulating interface electronic structure via metal oxides is developed. All the heterostructure catalysts present significant improvement of HER electrocatalytic activities, demonstrating a positive role of metal oxides decoration in promoting the rate‐limited water dissociation step for the HER mechanism in alkaline media. The as‐obtained MoS2/Ni2O3H catalyst exhibits a low overpotential of 84 mV at 10 mA cm−2 and small charge‐transfer resistance of 1.5 Ω in 1 m KOH solution. The current density (217 mA cm−2) at the overpotential of 200 mV is about 2 and 24 times higher than that of commercial Pt/C and bare MoS2, respectively. Additionally, these MoS2/metal oxides heterostructure catalysts show outstanding long‐term stability under a harsh chronopotentiometry test. Theoretical calculations reveal the varied sensitivity of 3d‐band in different transition oxides, in which Ni‐3d of Ni2O3H is evidently activated to achieve fast electron transfer for HER as the electron‐depletion center. Both electronic properties and energetic reaction trends confirm the high electroactivity of MoS2/Ni2O3H in the adsorption and dissociation of H2O for highly efficient HER in alkaline media. Through interfacial engineering, the earth‐abundant MoS2 based catalyst is synthesized with transition metal oxides. With the optimized electroactive interfaces with efficient electron transfer, the low overpotential for the hydrogen evolution reaction (HER) in the alkaline is realized in MoS2/Ni2O3H with long‐term durability. This indicates a new strategy of developing superior catalysts for HER in the harsh alkaline environment.